2018
DOI: 10.1128/aac.00023-18
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacterial Membrane Fatty Acid Composition on the Failure of Daptomycin To Kill Staphylococcus aureus

Abstract: Daptomycin is a last-resort membrane-targeting lipopeptide approved for the treatment of drug-resistant staphylococcal infections, such as bacteremia and implant-related infections. Although cases of resistance to this antibiotic are rare, increasing numbers of clinical,in vitro, and animal studies report treatment failure, notably againstStaphylococcus aureus. The aim of this study was to identify the features of daptomycin and its target bacteria that lead to daptomycin treatment failure. We show that daptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 60 publications
7
53
3
Order By: Relevance
“…Even when cultures were treated with an overkill of 25-100× MIC, it still took about 5 min to achieve maximum membrane depolarization and influx of the membrane-impermeable DNA-binding fluorescence dye Sytox green [74]. Similar results were found at 80× MIC using BacLight as a reporter [57]. In line with these findings on S. aureus, depolarization in Staphylococcus epidermidis occurred at 2-4× MIC after 60 min of treatment and it took 16× MIC to observe depolarization at only 15 min.…”
Section: Pore Formation In Vivosupporting
confidence: 60%
See 2 more Smart Citations
“…Even when cultures were treated with an overkill of 25-100× MIC, it still took about 5 min to achieve maximum membrane depolarization and influx of the membrane-impermeable DNA-binding fluorescence dye Sytox green [74]. Similar results were found at 80× MIC using BacLight as a reporter [57]. In line with these findings on S. aureus, depolarization in Staphylococcus epidermidis occurred at 2-4× MIC after 60 min of treatment and it took 16× MIC to observe depolarization at only 15 min.…”
Section: Pore Formation In Vivosupporting
confidence: 60%
“…A later study used different lipid mixtures, including 3:1 DMPC/DMPG and 1:1 POPC/POPG (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine/1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol), and found that daptomycin pores are likely selective for potassium ions [55]. In fact, some studies have observed potassium leakage from bacterial cells [56][57][58]. Several studies supported the model of a more or less organized daptomycin pore.…”
Section: Mechanism Of Action In Model Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…MRSA strains have acquired several Song et al AMB Expr (2020) 10:64 mechanisms to inactivate or block the effects of antibiotics. For example, formation of a thick biofilm can act as a physical barrier to antibiotics, and structural differences have also evolved, including variations in membrane composition and modifications of the target of antibiotics (Boudjemaa et al 2018;Craft et al 2019;Fishovitz et al 2014). Therefore, the antibiotic resistance of MRSA poses a significant treatment challenge and gaining greater insight into the mechanisms contributing to this resistance can help to guide treatment and control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm production is the response of bacteria to adverse environmental conditions [2], such as the presence of antibiotics, or the need to establish a chronic colonization [3][4][5]. The creation of a (thick) biofilm represents a physical barrier to antibiotics, and structural modifications can also develop in membrane composition and in the antibiotics' targets [6,7]. At present, microbial biofilm production represents a major economic and clinical problem, and its prevention and treatment are therefore a major concern.…”
Section: Introductionmentioning
confidence: 99%